If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2V + -14 = 14 Reorder the terms: -14 + 2V = 14 Solving -14 + 2V = 14 Solving for variable 'V'. Move all terms containing V to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 2V = 14 + 14 Combine like terms: -14 + 14 = 0 0 + 2V = 14 + 14 2V = 14 + 14 Combine like terms: 14 + 14 = 28 2V = 28 Divide each side by '2'. V = 14 Simplifying V = 14
| 1+3n=10 | | X=-2T^2-22T+48 | | 2-14=14 | | -8m-7=-7m | | X+.05x=10.5 | | 24-6x=4-x | | 4+y=12x-3y | | 6x^3+26x^2+8x=0 | | F(X)=-2T^2-22T+48 | | 14y-56= | | 7y-3+6y-7= | | 3+2a=9 | | (2x+5)(2x+5)=11 | | 13=3.14(3.14)(r^2) | | 10+2y=4 | | .75y-.66(0)=12 | | -2(3t-3)+3t=6t-5 | | 3+1.5(z+4)=3.5z-3 | | w-1.4=-6.3 | | 4a=3b-7 | | 5-3(x-3)=x+9 | | -2m+4=16+m | | 4x+y+x=180 | | 6(z+8)=5(z-2)+z | | 150=30-1p+9p | | 3=1.125X | | -16t^2+14t+270=0 | | -6x+7+7x=6+x+1 | | .75(0)-.66x=12 | | ae+n=p | | 0=2x^2+9x+4 | | 6k-(5+k)=-(3k+5) |